2017
DOI: 10.1002/alr.21942
|View full text |Cite
|
Sign up to set email alerts
|

How does the pattern of aeroallergen sensitization change over time across all ages?

Abstract: IgE sensitization to aeroallergens can change in individuals with allergy. These changes may be different according to the patient's age. If rhinitis symptoms or treatment efficacy changes, repeat IgE sensitization testing is needed to find changes in allergen sensitization patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Secondly, we showed that mite IgE sensitivity (SPT or specific IgE) decreased with age, as repeatedly reported [ 28 , 29 , 30 , 31 ]. In 2011, Scichilone and colleagues reviewed the available literature assessing the impact of age on atopy: the majority of the studies (i.e., 15 among 17) reported a decline of the prevalence of atopy with aging, associated with the immunosenescence process, in both healthy subjects and individuals affected by allergic respiratory diseases [ 31 ].…”
Section: Discussionsupporting
confidence: 84%
“…Secondly, we showed that mite IgE sensitivity (SPT or specific IgE) decreased with age, as repeatedly reported [ 28 , 29 , 30 , 31 ]. In 2011, Scichilone and colleagues reviewed the available literature assessing the impact of age on atopy: the majority of the studies (i.e., 15 among 17) reported a decline of the prevalence of atopy with aging, associated with the immunosenescence process, in both healthy subjects and individuals affected by allergic respiratory diseases [ 31 ].…”
Section: Discussionsupporting
confidence: 84%
“…The mechanism of IgE sensitization to aeroallergens can change depending on the patient’s age. 39 Unlike JCP, HDM and animal dander sensitizations are prominent in children, 40 and HDM tends to not become a newly sensitized antigen as a person grows to adulthood. 39 , 40 In addition, once HDM-specific IgE responses increase in childhood, it is difficult for decreases to occur.…”
Section: Discussionmentioning
confidence: 99%
“…39 Unlike JCP, HDM and animal dander sensitizations are prominent in children, 40 and HDM tends to not become a newly sensitized antigen as a person grows to adulthood. 39 , 40 In addition, once HDM-specific IgE responses increase in childhood, it is difficult for decreases to occur. 41 Therefore, adulthood HDM and animal dander-specific IgEs do not necessarily indicate accurately sensitizations in adulthood and it was difficult to draw a clear conclusion from the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the precise and accurate detection of allergens is important for treating (immunotherapy) and preventing (allergen avoidance) atopic diseases. Several studies have reported that inhalant allergen sensitization can be affected by various factors, including genetics, age, exposure time, concentration of allergens, and other unknown factors [1][2][3][4][5][6][7]. Addition-ally, recent global shifts in climate might significantly affect the incidence of atopic diseases.…”
Section: Introductionmentioning
confidence: 99%